Ongoing Challenges Faced by Expatriate Managers: An Exploratory Study of Expatriate Managers in Nigeria and Canada - Otoakhia, Aikenosi (2009)
This qualitative study will seek to uncover the concept of workforce diversity, to discover the effects of workforce diversity on an organization, to find out how the managers manage diverse workforces, to highlight the challenges faced by expat managers in managing a diverse workforce, and to identify the possible solutions to these challenges. Additionally, the study will compare the results of these aims between the workforces of Canada and Nigeria. Four research questions were developed to help guide the research, and are: (1) What is workforce diversity? (2) How does a diverse workforce impact an organization? (3) How do the managers manage a diverse workforce? (4) What are the challenges experienced by expat managers in managing a diverse workforce? The research questions will be addressed through the analysis of data that will be collected by interviewing 8 expat managers (three in Canada and five in Nigeria). Analysis of the data will include both phenomenology (to determine the themes and phenomena inherent to the managers lived experiences) and a comparative case study (to compare the results between the two countries). Chapter 1 provided an introduction and overview of the study. Chapter 2 discusses information regarding both Nigeria and Canada. Chapter 3 contains the literature review for this study. Chapter 4 describes in greater detail the research methodology to be used. Chapter 5 presents the data and the analysis of the data and contains the conclusions of the research, a discussion of the results, and a summary.